The efficacy of the legal and institutional framework for the manage ment of economic crimes in Uganda : a case study of the offences of embezzlement and causing financial loss - Komuhangi, Alice (Kampala, 2015)
Unpublished dissertation (LLM) - Makerere University, 2015.
Includes bibliogrpahical references (p. 94-96).
Keywords: Embezzlement -- Uganda